Endogenous Market Structures and Labor Market Dynamics - Andrea Colciago; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
We propose a model characterized by strategic interactions among an endogenous number of producers and search and matching frictions in the labor market. In line with U.S. data: (i) new firms account for a relatively small share of overall employment, but they create a relevant fraction of new jobs; (ii) firms entry is procyclical; (iii) price mark ups are countercyclical, while aggregate profits are procyclical. In response to a technology shock the labor share decreases on impact and overshoots its long run level. Also the propagation on labor market variables is stronger than in the standard search model. We argue that the countercyclicality of the price mark up is the key mechanism for our results.
Keywords: E24; E32; L11; 330; Endogenous Market Structures; Job Creation; Firms Entry; Search and Matching Frictions